A multimedia tennis instruction system: tracking and classifying swing motions. (1st January 2013) - Takano, Kosuke; Li, Kin Fun
Advances in data acquisition, human computer interface, and artificial intelligence have enabled the development of e-learning systems for educational and instructional purposes. Sport instruction, in particular, is a very attractive domain for computer-based learning as compared to the traditional human coaching approach, potentially saving space, time, and cost. A tennis instruction system has been designed and developed. In order to have a practical sport instructional system, motion-sensed input data must be accurately captured, cleansed, clustered, and classified, before further processing can be performed. This work presents the tennis instruction prototype and the issues associated with motion capture and identification.